ALLena: Thaw depth measurements of the active layer in the Lena River Delta region from 1998 to 2022, Northeastern Siberia, detailed table extquotesingleDetailed_data_TD_Nitzbon extquotesingle - Alexandra Veremeeva; Anne Morgenstern; Milena Gottschalk; Julia Jünger; Sebastian Laboor; Evgeny Abakumov; Irina Adrian; Michael Angelopoulos; Sofia Antonova; Julia Boike; Niko Bornemann; Alexandra Cherepanova; et al. (PANGAEA, 2025)
Active layer thickness (ALT) is one of currently two Essential Climate Variables related directly to permafrost regions as defined by the Global Climate Observing System (GCOS) at the World Meteorological Organization (WMO). ALT is determined as the maximum thaw depth at the end of the thawing season and is being monitored across the Arctic to better understand climate change impacts on landscape, permafrost, hydrology, vegetation, and soil biogeochemistry. In addition, spatially and/or temporally distributed measurements of thaw depth (TD) in the active layer during the thawing period are often recorded during field work in permafrost regions for various research purposes and process understanding. The ALLena dataset presents a compilation of thaw depth (TD) measurements of the active layer in the Lena River Delta region based on published and unpublished field data collected during Russian and joint German-Russian expeditions from 1998 to 2022. The dataset contains data from different areas of the Lena Delta region with clustering in research-intensive areas, e.g. in the vicinity of Research Station Samoylov Island, but also includes sites adjacent to the delta such as Muostakh Island, Bykovsky Peninsula and Tiksi settlement surroundings. The compiled data is distributed across various ecosystems and geomorphological units underlain by different types of deposits and characterized by various relief positions, microtopography, soil and vegetation cover (e.g. active floodplains, polygonal tundra on Holocene Lena Delta terraces, remnants of Yedoma Ice Complex, etc.). TD measurements were conducted as opportunistic single as well as targeted TD transects or grid measurements. For some sites measurements of TD were repeated at the same locations in different years. TD was measured one time per site or several times per site within a few centimeters to several meters to capture small-scale heterogeneity depending on e.g. microcrotopography or vegetation type. The main datatable (doi:10.1594/PANGAEA.973813) contains discrete TD values if they were measured one to three times per site. In case of more than three TD values per measurement site, the main datatable provides the minimum, maximum, and mean TD as well as the number of measurements that were averaged. For sites with more than three TD measurements per site, separate detailed tables like this one are provided. The dataset presents a highly valuable compilation of TD data over a uniquely large Arctic region and long time span. It might complement the Circumpolar Active Layer Monitoring (CALM) program and other published ALT and TD datasets for other permafrost regions and may be used for e.g. parametrization or validation of permafrost modelling and remote sensing studies.
In: Veremeeva, A et al. (2025): ALLena: Compilation of thaw depth measurements of the active layer in the Lena River Delta region from 1998 to 2022, Northeastern Siberia [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974408